Two types of insoles design to influence running biomechanics in opposite directions and individual responses - Patoz, Aurélien; Trastour, Loris; Gindre, Cyrille; Breine, Bastiaan; Lussiana, Thibault (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionGlobal running patterns vary along a spectrum defined by the degree of body verticality. This continuum ranges from extension (upright extended postures) to flexion (forward-leaning positions characterized by flexion at the hips and knees). Understanding these patterns is crucial for effective injury rehabilitation. Recent research has identified inefficiencies in vertical load management, leading to the development of extension- or flexion-based exercises. Insoles, while not typically designed for comprehensive extension or flexion adjustments, can complement these exercises. This study tested two novel insoles—extension and flexion—designed by a podiatrist based on principles such as higher shore values for enhanced extension increased thickness for greater flexion.MethodsEighteen recreational runners ran at 12 km/h on a treadmill under three conditions: no insole, extension insole, and flexion insole. We hypothesized that the extension insole would produce a lower duty factor (DF), greater vertical center of mass displacement (∆COM), and shorter time to maximum ankle pronation during ground contact (tmax⁡. pron) with opposite effects expected for the flexion insole.ResultsHowever, the results did not support this hypothesis, as no significant effects of either insole were observed on DF, ∆COM, or tmax⁡. pron compared to running without an insole (p ≥ 0.38). Additionally, there was considerable variation in individual responses to the insoles. The extension insole resulted in a more extended running pattern in 50% of participants, while the flexion insole produced a more flexed pattern in 44% of participants. Notably, only 11% of participants reported both a more extended running pattern with the extension insole and a more flexed running pattern with the flexion insole.DiscussionThe anticipated effects of the insoles on running mechanics were not consistently observed, underscoring the complexity of insole interventions. This highlights the need for further research to improve insole design, refine insole prescription, and to better understand the nuances of running biomechanics.